1991
DOI: 10.1007/bf02431053
|View full text |Cite
|
Sign up to set email alerts
|

Nature and distribution of manganese nodules from three sediment domains of the Central Indian Basin, Indian Ocean

Abstract: Abstract. Manganese nodules from the Central Indian Basin (5~176 vary in abundance, morphology, mineralogy, and chemistry with water depth and sediment type. Nodules from the southern region, dominated by siliceous sediment, differ markedly from northern and central regions, dominated by terrigenous and terrigenous-siliceous mixed sediments, respectively. Effects of iysocline and sediment diagenesis are envisaged for trace metal enrichment in rough nodules of the southern region. Influence of deep ocean bottom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…Out of the eleven piston cores, seven contained manganese micronodules, although there does not appear to be any pattern in the distribution of these cores over the surveyed area. The presence of micronodules is consistent with the findings of Bannerjee and Mukhopadhyay (1991) who observed that small (<4cm diameter) manganese nodules are most common north of 9°S, which would include this study area.…”
Section: Sediment Cores and Their Relationship To Echo Charactersupporting
confidence: 92%
“…Out of the eleven piston cores, seven contained manganese micronodules, although there does not appear to be any pattern in the distribution of these cores over the surveyed area. The presence of micronodules is consistent with the findings of Bannerjee and Mukhopadhyay (1991) who observed that small (<4cm diameter) manganese nodules are most common north of 9°S, which would include this study area.…”
Section: Sediment Cores and Their Relationship To Echo Charactersupporting
confidence: 92%
“…During their accretion from seawater, they concentrate various trace elements within the Fe–Mn oxide layers (Reyss et al, ). Even though several studies have described the geochemical and mineralogical characters of ferromanganese deposits from the Indian Ocean (Banerjee, ; Banerjee, ; Banerjee & Iyer, ; Banerjee, Iyer, & Dutta, ; Banerjee & Miura, , ; Banerjee & Mukhopadhyay, ; Banerjee & Mukhopadhyay, ; Banerjee, Roy, Dasgupta, Mukhopadhyay, & Miura, ; Bau & Koschinsky, ; Jauhari & Pattan, ; Pattan et al, ; Roy, Dasgupta, Mukhopadhyay, & Fukuoka, ; Tooms, Summerhayes, & Cronan, ; Vineesh, Nath, Banerjee, Jaisankar, & Lekshmi, ), the isotopic data on these deposits are still scanty. O'Nions, Frank, von Blanckenburg, and Ling () described the secular variation of Nd and Pb isotopes in ferromanganese crusts from the Central Indian Basin and compared them with those from the Atlantic and Pacific.…”
Section: Introductionmentioning
confidence: 99%